Asbestos Deaths: Sustainability Against Social Justice - Stefania Ferraro (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
This paper aims to analyze the contradictions between sustainability and social justice by examining the deaths caused by asbestos processing and the resulting environmental disasters in affected areas. In the first part, the author explores the contradictions between sustainable reforms and “performative environmentalism” as compared to integral ecology, which advocates an integrated and holistic approach to addressing political, social, economic, and environmental issues. Her analysis is grounded in a theoretical framework that argues sustainable development must be evaluated in its full complexity and contrasted with neoliberal simplification practices that prioritize efficiency and the economization of economically assessable resources. From this perspective, the second part of the paper discusses these issues through an Italian asbestos case study, viewed as an instance of social injustice conflicting with sustainability policies. The author outlines three main points demonstrating how sustainability governance can bypass any potential for social justice in situations involving asbestos processing. She explains that managing asbestos cases contributes to the normalization of environmental disasters and exacerbates the conflict between the right to work and the right to health. The incidents involving asbestos exemplify how sustainability is interpreted through a neoliberal lens.